PENGEMBANGAN PERANGKAT PENILAIAN BERBASIS KELAS UNTUK MATERI BANGUN RUANG SISI DATAR PADA KELAS VIII MTs - Sefrinal Sefrinal (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2016)
Assessment tool that used in the form paper and pencil test has not been able to assess students ability for whole. The purpose this study is to produce assesment tool based on class for bangun ruang sisi datar which is valid,practical and effective. The tool is expected to assess students ability for whole. The research conducted was a kind of research and development using a 4-D model consists of four stages, namely: 1) define, 2) design, 3) development, and 4) dissemination. Mathematics education, elementary education, and language experts examined the validation of the tool. The tool practicality was investigated by observing the lesson, filling questionnaire by the student, and conducting interviews with the students and teachers. The tool effectiveness was know from the learning activities and learning outcomes of the students. Finally, the data collected was analyzed descriptively. The result of the research showed that bangun ruang sisi datar tool generated is valid in terms of content and construct for the grade eighth junior high school students. The tool is practical as well since it is easy, clear, and can be used without problems. It can be concluded that the assesment tool based on classbangun ruang sisi datar is valid, practical, and effective